Busy Yet Socially Engaged: Volunteering, Work–Life Balance, and Health in the Working Population. Issue 2 (February 2015) - Ramos, Romualdo; Brauchli, Rebecca; Bauer, Georg; Wehner, Theo; Hämmig, Oliver
Abstract : Objective: To understand the relationship between volunteering and health in the overlooked yet highly engaged working population, adopting a contextualizing balance approach. We hypothesize that volunteering may function as a psychosocial resource, contributing to work–life balance and, ultimately, health. Methods: A total of 746 Swiss workers participated in an online survey; 35% ( N = 264) were additionally volunteers in a nonprofit organization. We assessed volunteering, work–life balance perceptions, paid job demands, and resources and health outcomes. Results: After controlling for job characteristics, volunteering was associated with less work–life conflict, burnout and stress, and better positive mental health. Results further revealed that balance perceptions partly explained the relationship between volunteering and health. Conclusions: Volunteering, albeit energy and time-consuming, may contribute to a greater sense of balance for people in the workforce, which might, in turn, positively influence health.